Antichlamydial Antibodies, Human Fertility, and Pregnancy Wastage - Amanda J. Stephens; Mira Aubuchon; Danny J. Schust (Hindawi Limited, 2011)
Genital infections with Chlamydia trachomatis (C. trachomatis) continue to be a worldwide epidemic. Immune response to chlamydia is important to both clearance of the disease and disease pathogenesis. Interindividual responses and current chlamydial control programs will have enormous effects on this disease and its control strategies. Humoral immune response to C. trachomatis occurs in humans and persistent antibody levels appear to be most directly correlated with more severe and longstanding disease and with reinfection. There is a close correlation between the presence of antichlamydial antibodies in females and tubal factor infertility; the closest associations have been found for antibodies against chlamydial heat shock proteins. The latter antibodies have also been shown to be useful among infertile patients with prior ectopic pregnancy, and their presence has been correlated with poor IVF outcomes, including early pregnancy loss. We review the existing literature on chlamydial antibody testing in infertile patients and present an algorithm for such testing in the infertile couple.